Activation of SnRK2 by Raf-like kinase ARK represents a primary mechanism of ABA and abiotic stress responses. Issue 2 (4th December 2020) - Islam, Mousona; Inoue, Takumi; Hiraide, Mayuka; Khatun, Nobiza; Jahan, Akida; Kuwata, Keiko; Katagiri, Sotaro; Umezawa, Taishi; Yotsui, Izumi; Sakata, Yoichi; Takezawa, Daisuke
Abstract: The Raf-like protein kinase abscisic acid (ABA) and abiotic stress-responsive Raf-like kinase (ARK) previously identified in the moss Physcomitrium ( Physcomitrella ) patens acts as an upstream regulator of subgroup III SNF1-related protein kinase2 (SnRK2), the key regulator of ABA and abiotic stress responses. However, the mechanisms underlying activation of ARK by ABA and abiotic stress for the regulation of SnRK2, including the role of ABA receptor-associated group A PP2C (PP2C-A), are not understood. We identified Ser1029 as the phosphorylation site in the activation loop of ARK, which provided a possible mechanism for regulation of its activity. Analysis of transgenic P. patens ark lines expressing ARK-GFP with Ser1029-to-Ala mutation indicated that this replacement causes reductions in ABA-induced gene expression, stress tolerance, and SnRK2 activity. Immunoblot analysis using an anti-phosphopeptide antibody indicated that ABA treatments rapidly stimulate Ser1029 phosphorylation in the wild type (WT). The phosphorylation profile of Ser1029 in ABA-hypersensitive ppabi1 lacking protein phosphatase 2C-A (PP2C-A) was similar to that in the WT, whereas little Ser1029 phosphorylation was observed in ABA-insensitive ark missense mutant lines. Furthermore, newly isolated ppabi1 ark lines showed ABA-insensitive phenotypes similar to those of ark lines. Therefore, ARK is a primary activator of SnRK2, preceding negative regulation by PP2C-A in bryophytes, which provides a prototype mechanism for ABA and abiotic stress responses in plants. Abstract : Phosphorylation in the activation loop of the Raf-like kinase ARK is critical for SNF1-related protein kinase2 regulation during abscisic acid responses in the moss Physcomitrium ( Physcomitrella ) patens .